Une médiation paysagiste comme support de recherche : l’expérience de l’atelier des paysages en vallée de l’Ance - Alexis Pernet (Projets de Paysage)
The grounds of the European Landscape Convention give to the authorities a role of traduction of publics aspirations and lead questions about the professionnal practices in landscape planification. This article presents an experimental mediation process led in the Ance valley (Parc naturel régional Livradois-Forez, France) and gives interrogations about its results, such as the attitude of the researcher in a competence situation. It presents a research diary as reflexion support and valuation method in the frame of an applied research.